2022
DOI: 10.1002/ardp.202200356
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of novel xanthene‐based thiazoles as potential antidiabetic agents

Abstract: A series of xanthene-based thiazoles was synthesized and characterized by different scpectroscopic methods, i.e. Proton nuclear magnetic resonance( 1 H NMR), carbon nuclear magnetic resonance ( 13 C NMR), infrared spectroscopy, carbon hydrogen nitrogen analysis, and X-ray crystallography. The inhibition potencies of 18 newly synthesized thiazole derivatives were investigated on the activities of acetylcholinesterase (AChE), butyrylcholinesterase (BChE), α-amylase (α-Amy), and α-glycosidase (α-Gly) enzymes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…It accelerates the conversion of glucose from starch and disaccharides. This enzyme break down the body‘s intake of carbs into simple molecules of glucose, which are then transported for intestinal absorption and ultimately result in hyperglycemia, an increase in blood sugar levels [1,2] . A dangerous metabolic illness called diabetes is characterized by elevated blood sugar levels.…”
Section: Introductionmentioning
confidence: 99%
“…It accelerates the conversion of glucose from starch and disaccharides. This enzyme break down the body‘s intake of carbs into simple molecules of glucose, which are then transported for intestinal absorption and ultimately result in hyperglycemia, an increase in blood sugar levels [1,2] . A dangerous metabolic illness called diabetes is characterized by elevated blood sugar levels.…”
Section: Introductionmentioning
confidence: 99%
“…It raises blood glucose levels in animals by converting starch and disaccharides into soluble monosacchar-ides like glucose. [5,6] Because of this role, α-glycosidase has been proposed as a potential therapeutic target for the treatment of type-2 diabetes in people. By slowing down the digestion of carbohydrates and subsequently the absorption of monosaccharides, inhibition of this enzyme may lower postprandial plasma glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this role, α-glucosidase has been proposed as a potential therapeutic target for the treatment of type-2 diabetes in people. [14,15] In the literature, it is observed that many newly synthesized organic compounds including isatin mannich bases, [16] tetrahydropyrimidine-5-carboxylates, [17] diaryl ethers, [18] 4,5-disubstituted-2-thioxo-1,2,3,4-tetrahydropyrimidines, [19] bromophenols, [20] cyclic thioureas, [21] sulfamides derived from βbenzylphenethylamines, [22] new amides and thiazolidineones synthesized on an acetophenone base, [23] aminomethyl and alkoxymethyl derivatives, [24] 2-hydroxyethyl substituted NHC precursors, [25] phloroglucinol derivatives, [26] novel N,N'-biscyanomethylamine and alkoxymethylamine derivatives, [27] Meta-cyanobenzyl substituted benzimidazoles, [28] novel amides of 1,1-bis-(carboxymethylthio)-1-arylethanes, [29] novel trischalcones, [30] imidazole derivatives, bis-sulfone derivatives, [31] novel benzo[b]xanthene derivatives, [32] nitrogen, phosphorus, selenium and sulfur-containing heterocyclic compounds, [33] Schiff bases containing phenol ring, [34] and piperazine derivatives [35] effectively inhibit AChE and BChE enzymes. All of these newly synthesized molecules, which inhibit both cholinergic enzymes, contain many functional groups that are important for biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…It raises blood glucose levels in animals by converting starch and disaccharides into soluble monosaccharides like glucose. Because of this role, α‐glucosidase has been proposed as a potential therapeutic target for the treatment of type‐2 diabetes in people [14,15] …”
Section: Introductionmentioning
confidence: 99%